2010
DOI: 10.1186/cc9308
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoncotic colloids and acute kidney injury: a meta-analysis of randomized trials

Abstract: IntroductionIt has been hypothesized that hyperoncotic colloids might contribute to acute kidney injury (AKI). However, the validity of this hypothesis remains unclear.MethodsA meta-analysis was conducted of randomized controlled trials evaluating AKI after infusion of hyperoncotic albumin and hydroxyethyl starch (HES) solutions. Mortality was a secondary endpoint. Eligible trials were sought by multiple methods, and the pooled odds ratios (OR) for AKI and death and 95% confidence intervals (CI) were computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 55 publications
2
64
0
5
Order By: Relevance
“…5 Odeljenje bolničke farmacije, Bolnica Valjevo, Valjevo, Srbija; 6 Institut za kardiovaskularnu hirurgiju "Dedinje", Beograd, Srbija KRATAK SADRŽAJ Cilj ra da Mo gu ći ri zik od po ve ća nja mor ta li te ta zbog pri me ne hu ma nih al bu mi na (HA) kod operi sa nih bo le sni ka još ni je utvr đen. Cilj ove stu di je bio je pro ce na udru že no sti sto pe mor ta li te ta ope ri sa nih bo le sni ka sa dru gim po ka za te lji ma kva li te ta zdrav stve nih uslu ga, po tro šnjom HA i hi drok si e til-skro ba (HES).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…5 Odeljenje bolničke farmacije, Bolnica Valjevo, Valjevo, Srbija; 6 Institut za kardiovaskularnu hirurgiju "Dedinje", Beograd, Srbija KRATAK SADRŽAJ Cilj ra da Mo gu ći ri zik od po ve ća nja mor ta li te ta zbog pri me ne hu ma nih al bu mi na (HA) kod operi sa nih bo le sni ka još ni je utvr đen. Cilj ove stu di je bio je pro ce na udru že no sti sto pe mor ta li te ta ope ri sa nih bo le sni ka sa dru gim po ka za te lji ma kva li te ta zdrav stve nih uslu ga, po tro šnjom HA i hi drok si e til-skro ba (HES).…”
Section: Discussionunclassified
“…In trauma and sepsis, cardiac index and oxygenation were higher after the administration of HES than hyperoncotic HA, but survival was unaffected by hyperoncotic HA. Furthermore, Wiedermann et al [6] suggested in their meta-analysis that renal effects of colloid solutions appeared to be dependent on the type of colloids. Hyperoncotic HA exerts renoprotection while hyperoncotic HES shows nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study did not use the correct patient numbers from the original ALBIOS study publication [48]. In contrast to hyperoncotic HES solution, no negative impact of albumin on renal function could be shown [49].…”
Section: Albuminmentioning
confidence: 99%
“…In a large multi-centre European study of 822 critically ill adults with shock receiving fluid resuscitation, use of hypertonic natural and synthetic colloids was associated with a several fold increased risk for AKI and death [50] . A recent systematic review found divergent findings for use of hyperoncotic colloids for resuscitation and subsequent risk of AKI [51] . In this meta-analysis of 7 trials including 1220 patients, hyperoncotic albumin was associated with reduced risk (OR = 0.24, P < 0.001); whereas hyperoncotic HES solutions were associated with increased risk for AKI (OR = 1.92; 95%CI: 1.31-2.81, P < 0.001).…”
Section: Colloid Solutionsmentioning
confidence: 99%